Tax loss offset restrictions: Last resort for the treasury? An empirical evaluation of tax loss offset rectrictions based on micro data - Nadja Dwenger (Arbeitskreis Quantitative Steuerlehre (arqus), 2008)
In Germany, the tax loss carry-forward of corporations significantly increased over the last decade. At the same time only a small percentage of losses have been effectively offset. One potential reason for this puzzle is that stricter loss offset restrictions have been introduced in recent years. I use a newly developed micro simulation model for the German corporate sector to evaluate the fiscal effects of these restrictions. Additionally, distributional breakdowns are provided. I find that the restrictions on the use of tax loss carry-back are rather ineffective while the newly introduced minimum taxation considerably increases yearly tax revenue by 1.1 billion exteuro.
Keywords: H25; C8; 330; micro simulation; loss offset restrictions; corporate taxation; tax loss carryforward; tax loss carry-back